Kunst der ersten Jahrhunderthälfte - 1900 bis 1960 : Bestandskatalog. (Mönchengladbach : Städtisches Museum Abteiberg, 1990)
Barlach, Ernst ; Beckmann, Max ; Dahmen, Karl Fred ; Heckel, Erich ; Kerschbaumer, Anton ; Klee, Paul ; Kupka, Frank ; Macke, August ; Man Ray ; Marini, Marino ; Meistermann, Georg ; Moeschlin, Walter Johann ; Nauen, Heinrich ; Nebel, Otto ; Pankok, Otto ; Pechstein, Hermann Max ; Poliakoff, Serge ; Rohlfs, Christian ; Rouault, Georges ; Schneider, Gérard ; Schumacher, Ernst ; Seewald, Richard ; Strater, Josef ; etc.
boek